One Day - Haarløv Johnsen, Ditte (Denmark : Den Danske Filmskole, 2007)
She is a beautiful, strong, 36 years old, migrant from West Africa, lives in the suburbs of Copenhagen and works as a prostitute. Each month she sends money home to the family that she misses constantly. She finds both solace and sacrifice through her cell phone, connecting with the family and daughter she hasn’t seen in six years, yet always remaining available to clients. This film presents the life of a woman who has sacrificed herself and her body in order to secure her family.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films